Associations of the serum kynurenine pathway metabolites with P50 auditory gating in non-smoking patients with first-episode schizophrenia - Yang, Qingyan; Zhang, Yong; Yang, Kebing; Niu, Yajuan; Fan, Fengmei; Chen, Song; Luo, Xingguang; Tan, Shuping; Wang, Zhiren; Tong, Jinghui; Yang, Fude; Li, Chiang-Shan R.; et al. (Frontiers in Psychiatry, 2022)
Objective: Our study aimed to investigate the associations between the serum level of kynurenine pathway (KP) metabolites and auditory P50 gating in non-smoking patients with first-episode schizophrenia (FES). Methods: In this study, eight two non-smoking patients with FES and 73 healthy controls (HC). P50 sensory gating was measured using the fully functional digital 64-channel EEG system, and the components included S1 amplitude, S2 amplitude, gating ratio (S2/S1), and amplitude difference (S1-S2). The serum levels of kynurenine and kynurenine acid were assessed using a combination of liquid chromatography with tandem mass spectrometry. The psychopathology was assessed by Positive and Negative Syndrome Scale (PANSS). Results: The serum kynurenine (251.46 ± 65.93 ng/ml vs. 320.65 ± 65.89 ng/ml, t = -6.38, p < 0.001), and kynurenine acid levels (5.19 ± 2.22 ng/ml vs. 13.26 ± 4.23 ng/ml, t = -14.73, p < 0.001), S1 amplitude [2.88 (1.79, 3.78) μV vs. 3.08 (2.46, 4.56) μV, Z = -2.17, p =0.030] and S1-S2 [1.60 (0.63, 2.49) μV vs. 1.92 (1.12, 2.93) μV, Z = -2.23, p = 0.026] in patients with FES were significantly lower than those in HC. The serum kynurenine and kynurenine acid levels were negatively associated with S1-S2 (r = -0.32, p = 0.004 and r = -0.42, p < 0.001; respectively) and positively correlated with S2/S1 ratio (r = 0.34, p = 0.002 and r = 0.35, p = 0.002; respectively) in patients. Conclusions: Our findings suggested that neuroactive metabolites of the KP might play an important role in sensory gating deficit in first episode patients with schizophrenia. Furthermore, metabolites of the KP may be a new target for the treatment of cognitive impairments in schizophrenia